Water masses distribution offshore the Sabrina Coast (East Antarctica) - Bensi, M; Kovacevic, V; Donda, F; O'Brien, PE; Linda Armbrecht; Armand, LK (2022)
Current glacier melt rates in West Antarctica substantially exceed those around the East Antarctic margin. The exception is Wilkes Land, where for example Totten Glacier underwent significant retreat between 2000 and 2012, underlining its sensitivity to climate change. This process is strongly influenced by ocean dynamics, which in turn changes in accordance with the evolution of the ice caps. Here, we present new oceanographic data (temperature, salinity, and dissolved oxygen) collected during austral summer 2017 offshore the Sabrina Coast (East Antarctica) from the continental shelf break to ca 3000 m depth. This area is characterized by very few oceanographic in situ observations. The main water masses of the study area, identified by analysing thermohaline properties, are the Antarctic Surface Water with potential temperature ∘C and salinity S<34.2 (σθ<27.55 kg m−3), the Winter Water with ∘C and (potential density, kg m−3), the modified Circumpolar Deep Water with θ>0 ∘C and S>34.5 (σθ>27.7 kg m−3), and Antarctic Bottom Water with ∘C and (; neutral density γn>28.30 kg m−3). The latter is a mixture of dense waters from the Ross Sea and Adélie Land continental shelves. Such waters are influenced by the mixing processes they undergo as they move westward along the Antarctic margin, also interacting with the warmer Circumpolar Deep Water. The spatial distribution of water masses offshore the Sabrina Coast also appears to be strongly linked with the complex morpho-bathymetry of the slope and rise area, supporting the hypothesis that downslope processes contribute to shaping the architecture of the distal portion of the continental margin.